Anti-influenza response achieved by immunization with a synthetic conjugate. - Müller, G M (1982)
The peptide corresponding to sequence 91--108 of the hemagglutinin of type A H3N2 influenza virus has been synthesized by the solid-phase peptide synthesis method and covalently attached to several macromolecular carriers. The conjugate with tetanus toxoid was used for immunization of rabbits and mice. The immunoglobulin fraction of the rabbit antiserum showed the presence and antipeptide antibodies by both agar gel diffusion and radioimmunoassay. In the latter assay, the antibodies showed marked crossreactivity with the intact virus of the A/Texas/77 strain. The antibodies were also capable of inhibiting the hemagglutination of chicken erythrocytes by the virus; the highest hemagglutination inhibition titer (1:32) was achieved with a serum-resistant strain of A/Texas/77. When the in vitro virus plaque formation assay was used with monolayers of Madin--Darby canine kidney (MDCK) cells, the number of plaques was reduced on interaction with the immunoglobulin fraction of the antiserum, which was effective up to a dilution of 1:32. Preliminary results indicate that C3H/DiSn mice immunized with the peptide--tetanus toxoid conjugate are partially protected against a further challenge with A/Texas mouse-adapted influenza virus. The results are thus indicative of the efficacy of the synthetic material in eliciting anti-influenza immune response.